2007
DOI: 10.1159/000101357
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Lymphocyte Subset Changes in the Peripheral Blood of Healthy Children – a Meta-Study

Abstract: Immunophenotyping is an important diagnostic tool for decision making in various diseases. Although clinical interpretation relies on measurable aberrations of the patient’s values from normal ranges, agedependent are rarely available. Materials and Methods: The present study is aimed to combine published data about normal values of peripheral blood lymphocyte subpopulations to describe age-dependent changes from the neonate to the adult. These values could serve in a better way as normal values in comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 59 publications
3
19
0
1
Order By: Relevance
“…The 3m samples were obtained at average 9 months after the surgery. At an age similar to our study group normal maturation leads to a decrease in B-cell count (44,45). Therefore, this decrease may be due to normal age related changes.…”
Section: Mp-induced B-cell Loss In the Follow-upsupporting
confidence: 82%
“…The 3m samples were obtained at average 9 months after the surgery. At an age similar to our study group normal maturation leads to a decrease in B-cell count (44,45). Therefore, this decrease may be due to normal age related changes.…”
Section: Mp-induced B-cell Loss In the Follow-upsupporting
confidence: 82%
“…Of note the choice of thresholds will dramatically impact the amount of failed analyses by flow, although they should be adapted to the specificity and the sample population of each laboratory. Indeed, as an example, our higher cut-off for B lymphocytes were different between adults (0.48 3 10 9 /l) and children (3.03 3 10 9 /l) and have to be adapted to each laboratory and calculated on larger cohorts (22,23).…”
Section: Original Articlementioning
confidence: 99%
“…The development from neonate to adult massively influences the composition of peripheral blood leukocytes as well as that of the lymphocytes. Counts and subset distribution of lymphocytes in children are different from that in adults, with all lymphocyte subsets undergoing substantial dynamic change in the first year of life (Sack et al, 2007). Moreover it has been demonstrated that relative percentages of CD19 + B-lymphocytes increase during the first 5 months of life, and remain stable until ≈ age 5-years (followed by a gradual decrease to adulthood).…”
Section: Introductionmentioning
confidence: 99%